Analysis of coordinated development of "society-ecology-policy" and spatio-temporal variation of people's livelihoods and well-being in the Yellow River basin, China. (April 2023) - Ren, Jing; Li, Yao; Zhang, Jiyue; Zhao, Lei; Guo, Jingmei; Du, Maohua; Hao, Chunxu; Hu, Rui
Graphical abstract: Mechanism of "Society-Ecology-Policy" Ternary System for People's Livelihood and Well-being. Highlights: Innovative integration of policy elements into coupling coordinated development. Discussion on the impact of economy and ecology on people's livelihood and well-being. Social development & ecological protection have negative effect in current period. Efficient response-implement of policy is key to people's livelihood & well-being. Shandong has the highest level of comprehensive development. Abstract: Since 2008, people's livelihoods and well-being has undergone profound changes, especially the Yellow River basin in China. Under the background of coordinated development, it is of great significance to research the temporal-spatial variation mechanism of people's livelihoods and well-being. This study establishes a "society-ecology-policy" ternary system to analyze the coordinated development in nine provinces situated along the Yellow River from 2009 to 2018. Furthermore, it explores the system's coordinated development mechanism with respect to people's livelihoods and well-being in different regions based on the geographically and temporally weighted regression theory(GTWR). The results were as follows. First, the impacts of social development ( SDi ), watershed ecological protection ( WEPi ), and policy support ( PSi ) in the middle and lower reaches are generally stronger than those in other regions. Shandong showed the highest average comprehensive benefit. Second, from the perspective of coupling coordinated development, Qinghai and Shanxi were classified as slightly uncoordinated; Sichuan, Ningxia, Gansu, Shanxi, Shaanxi, and Henan were basically coordinated; and Inner Mongolia and Shandong were moderately coordinated. Third, clear temporal-spatial differences existed in the impact of degrees of coordinated development on people's livelihoods and well-being. Social development provided a driving force for the economy, yet excessive use of natural resources had a significant negative impact. While ecological debt and long payback periods of environmental protection investment may negatively impact people's livelihoods and well-being, the rapid response and precise execution of policies are key guarantees for improving the same.